Konsumsi Bubur Kacang Hijau Meningkatkan Berat Badan Balita Gizi Kurang - Nenobais, Lina Dias Tifina; Widayati, Rina Sri (Jurnal Kebidanan Malakbi, 2025)
Undernutrition significantly impacts child development in Indonesia, with a prevalence of 17.1% among toddlers. Malnutrition in early childhood has severe consequences, including increased mortality, higher healthcare costs, and impaired cognitive development. This study investigates the potential of nutrient-rich mung bean porridge to improve weight gain in malnourished toddlers, addressing a critical public health challenge. Recognizing the crucial role of nutrition in early childhood, this study investigates the potential of mung bean porridge as a nutritional intervention to improve weight gain in malnourished toddlers receiving treatment at PT. Sumur Pandanwangi Clinic. Mung beans are a rich source of essential nutrients, including carbohydrates and protein, making them a promising candidate for addressing nutritional deficiencies in this vulnerable population. This study aimed to determine the effect of mung bean porridge on weight gain in malnourished toddlers treated at PT. Sumur Pandanwangi Clinic using a pre-experimental framework with a One Group Pretest-Posttest Design. A total of 20 research participants were selected using Consecutive Sampling. Weight measurements were obtained using a digital scale, and observations were recorded on standardized sheets. The data collected were analyzed using the Paired-t Test. The study found that the average weight of toddlers before receiving green bean porridge was 10,955 grams. After consuming the green bean porridge, their weight increased to 11,080 grams, marking an increase of 125 grams. Subsequent analysis demonstrated a significant effect of the green bean porridge on weight gain among malnourished toddlers. The findings yielded a p-value of 0.001, which is statistically significant as it falls below the threshold of 0.05. This study demonstrates the effectiveness of mung bean porridge in improving weight gain in malnourished toddlers. The significant weight increase observed among participants provides strong evidence for its use as a cost-effective and locally available nutritional intervention to address undernutrition in Indonesia.